Pemanfaatan Bittern Dan Cuka Sebagai Koagulan Pada Pembuatan Tahu - Sri Ratna Dewi; Resti Handayani; Abu Bakar; Saifullah Ramli (Jurnal Inovasi Ramah Lingkungan, 2022)
Salt waste known as bittern found in the village of  Baet Aceh Besar Regency is one type of liquid waste that has substantial benefits and is re-utilized as a coagulant on the manufacture of tofu. Tofu is a kind of processed products of soybeans. Its manufacture process requires coagulant as a coagulant substance. This study used waste from the production of salt as a coagulant namely bittern as well as vinegar to compare. In this study, Bittern was used as a clot on the tofu manufacture process. The results showed that the addition of bittern coagulant in the tofu manufacture process was better than with coagulant of vinegar. The best result of coagulant is when it has 2% concentration and in 20 minutes. It is proven in chemical test that on test of water content obtained value about 83%, ash content test was 3% and 16% protein test while fat content was 11%.